Strategi pengelolaan kelas dalam meningkatkan hasil belajar siswa pada kelas 5 ICP MINU Tratee Putera Gresik - Alviani, Fauziah Ninik (Maliki Interdisciplinary Journal, 2024)
Classroom management is one of the most challenging aspects of the educational process, attracting the attention of both experienced and new teachers. This research aims to explore effective classroom management techniques and the factors that influence their success at MINU Tratee Putera Gresik. Good classroom management involves arranging physical space, managing student behavior, and developing communication skills aimed at creating a conducive and efficient learning environment. Through direct observation in class 5 ICP, it was found that the formation of a classroom organizational structure and seating arrangements as well as teaching tools were very important in supporting a conducive learning atmosphere. In addition, this research identifies the challenges teachers face in classroom management, including diverse responsibilities and limited teaching and learning time. By applying appropriate classroom management principles, teachers can create an efficient learning environment, support student development, and increase the effectiveness of learning activities.